The propagation of sustainable fishery by Arctic shipping route stakeholders. (September 2021) - Zhao, Changping; Xie, Xiya; Gong, Yu; Liu, Beili
Abstract: This research addresses the question of how to better disseminate the concept of sustainable fishery along the Arctic shipping route. The fishery trade network of Arctic is constructed and the complex network theory is applied to conduct the analysis. We further simulate the network by introducing three factors, namely, national will, knowledge absorption capacity and initial propagation node and applying the SIR (susceptible–infective-removed) model. It is found that, in order to disseminate the sustainable fishery concept in the Arctic shipping route, there is a need for countries to increase their national will, increase their capacity to absorb knowledge, and give full play to the role of high-node countries. This paper theoretically suggests three countries of Norway, Denmark, and China to act as initiators of the network and proposes possible measures that countries can take to cooperate on sustainable fisheries development. Our findings offer a useful reference on international arctic fishery cooperation. Highlights: Better disseminate the concept of sustainable development in the Arctic region. Complex network theory to construct fishery trade network of Arctic. Norway, Denmark, and China to act as initiators of the network. Policy recommendations on international Arctic fishery cooperation.